Predation of Columbina squammata Lesson, 1831 (Aves: Columbidae) by Cariama cristata Linnaeus, 1766 (Aves: Cariamidae) - Moreira, Sandro Gonçalves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The present paper reports the first record of predation of the scaled dove (Columbina squammata Lesson, 1831) by red-legged seriema (Cariama cristata Linnaeus, 1766), in the countryside of the municipality of Uberlândia, Minas Gerais, Brazil.
Keywords: Red-legged seriema; Scaled dove; Ecological relations